دراسة توزع وخصائص ثمار نخلة التمر حسب الإتجاهات - قعري, أحمد العيد; عويسي, عبد الرحمان; غرايري, ابراهيم (جامعة الوادي - University of Eloued, 2022)
This study aims to determine the distribution and characteristics of the date palm fruits according to the trends in the OuedSouf region, by comparing the quantitative and morphological characteristics of the fruits in different regions of the north, south, east and west. , this study was carried out on three varieties of date palm Al-Ghars, DagletNour and Daglet White. Where this study allowed to evaluate the discrepancy between the fruits of the three studied varieties according to trends . The results showed a great diversity between the characteristics of the fruits according to the varieties and trends, where we found that the largest average length of the fruit on the east side was estimated at 3.82 cm, and the lowest average length in the south was estimated at 3.63 cm. As the average weight of the whole fruit, the lowest weight on the eastern side was estimated at 5.67g , and the largest weight on the western side was estimated at 6.24g. A difference was also found in the average length of the kernel, which ranges from 2.37 in the east to 2.74 cm in the north. On the other hand, we found a difference in the weight of the kernel, which ranges from 5.15 g from the north side to 5.37 from the west side. As for the average number of Arjoun Dates , we found the largest number on the south side, estimated at 5Arjoun Dates, and the lowest number on the north side, estimated at 2Arjoun Dates. We also recorded the largest number of Arjouns at Deglat White, and the least of it was DegletNour. The results showed that the average number of shamrocks per Arjun varies according to trends and varieties, where the largest number recorded in the north was 78 shamrocks, and the lowest number was in the western side with 68 shamrocks, and the largest number was recorded in Al-Ghars variety and the lowest in the DeglatNour variety. As for the number of fruits, it was greater in the west, it was estimated at 28 fruits in AlShamroukh, and the lowest number in the east with 16 fruits in Al-Shamroukh. As for the mineral content of the fruits, where the largest percentage was in the west with a capacity of 2.16%, and the lowest percentage in the south was 1.46%. In the end, we concluded that the north side produces less fruits compared to the rest of the regions, and it is the best in terms of the quality of fruits .
التنوع الحيوي وفيزيولوجيا النبات
Keywords: النخيل، النواة، التمور; date palms; kernels; dates; quantitative characteristics; studied varieties (DegletNour; Deglet White; Al-Ghras); directions